Hopeful Resistance and Solidarity from Below in Imbolo Mbue's How Beautiful We Were - Suárez-Rodríguez, Ángela (Complutense Journal of English Studies, 2024)
By examining the discourse of hope and resistance in Imbolo Mbue’s How Beautiful We Were (2021), which portrays the emergence of a solidarity movement and protest in a fictional West African country, this article engages with the theory of political solidarity within the framework of contemporary African necropolitics. The acts of resistance carried out by the protagonists against their government, which exposes them to death at the hands of Western neocolonialism, show the capacity of the African oppressed majority to work together for an improvement in their living conditions in a spirit of hope, namely through building solidarity networks as a strategy of subversion and survival. In this sense, though different forms of solidarity surface throughout the narrative, my contention is that Robin Zheng’s (2023) notion of “solidarity from below” as a form of power available to the otherwise powerless is the one that prevails. More specifically, the tragic ending of the story allows to critically reflect on Zheng’s debate on the limitations of group emotional cohesion to achieve sociopolitical transformation. Along these lines, I identify this novel as a literary call for renewed forms of African political solidarity that must be necessarily forged and maintained by the oppressed masses not merely through hope but, essentially, through radical love.